Emergency physicians spend more time caring for patients who prefer a language other than English which may not be accounted for in reimbursement structures - Martin A. Reznek; Jennifer Edwards; Sean S. Michael; Jacqueline Furbacher; Alexandra Sanseverino; Payal K. Modi; Kevin A. Kotkowski; Celine Larkin (Journal of the American College of Emergency Physicians Open)
Abstract Background Emergency departments increasingly serve patients who prefer a language other than English. Honoring patients’ language preferences is crucial for quality and cultural appropriateness of care. We sought to assess whether time spent in caring for patients who preferred a language other than English differed from patients whose language preference was English. Secondarily, we sought to assess professional reimbursement across the two groups. Methods We retrospectively analyzed an existing dataset from a time‐in‐motion study that included direct observation measurements of emergency physicians’ time spent during patient encounters. Our primary outcome was physician time spent conducting patient care, comparing patients who preferred a language other than English to patients who preferred English. Secondarily, we sought to assess if relative value unit (RVU)‐based compensation differed across the two groups. We calculated descriptive statistics and performed multivariable regression. Results Across 218 patient encounters, physicians spent 18.6% longer on encounters with patients whose preferred a language other than English (median = 18.5 min, interquartile range [IQR] 14.8–27.9 min) than for those who preferred English (median = 15.6 min, IQR 11.5–22.9 min; p = 0.04). After controlling for other factors, patients’ preferred language was not associated with increased RVUs (β = −0.12, t = −1.94, p = 0.055). Conclusions Emergency physicians appear to spend more time caring for patients who prefer a language other than English. This additional effort during the care of this potentially vulnerable population may not be reflected in past and current reimbursement structures. Additional research is prudent as we seek to better address social determinants of health in care delivery and reimbursement systems.